Social embeddedness as a trigger of business tourism cooperation - Czernek-Marszałek, Katarzyna; Marszałek, Paweł (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2020)
Cooperation between individual actors from a given tourist destination is a necessity under contemporary conditions. Its establishment and development can be triggered by many factors, and the social embeddedness of tourism entrepreneurs in the local community can be considered one of them. This factor is likely to be of special importance as social aspects are very important in the tourist sector. The aim of the paper is to present and assess the impact of social embeddedness on business cooperation in dyads and networks. The analysis was conducted using the case of a partnership structure in the south of Poland. To achieve the research aim, Social Network Analysis (SNA) was employed. The paper exploits an approach very rarely used in tourism empirical research, which combines two types of SNA– qualitative and quantitative. The research confirmed the role of social embeddedness as a trigger for cooperation in a tourist destination
Argumenta Oeconomica, 2020, Nr 1 (44), s. 341-386